Research Trends on the Use of E-LKM in Education Research in Indonesia: Bibliometric Analysis - Rahmiati, Devi; Sarwi; Widiyatmoko, Arif (Universitas Negeri Semarang, 2025)
This research aims to analyze the main research trends, collaboration patterns, and dominant themes in research regarding the use of e-LKM in educational research in Indonesia in the last 5 years (2018–2023) using a bibliometric analysis approach. Data collection through searches based on titles, abstracts and article keywords from Google Scholar and ERIC databases in the last 5 years. The article selection process is carried out systematically using the PRISMA method to ensure data transparency and validity with the help of the VOSviewer application. The results show that the research trend on the use of e-LKM has experienced a significant increase in the number of publications since 2020, mainly driven by the need for distance learning during the COVID-19 pandemic. The pattern of collaboration between researchers shows that there is a strong synergy in several institutions and regions that contribute greatly to research productivity, such as Universitas Negeri Riau, Universitas Mataram and STKIP Bima as the main contributors. The mapping of the research theme uses a co-word network through VOSviewer to identify four main clusters, including: (1) examining the effectiveness and barriers in the practice of using e-LKM in the real classroom, both from the lecturer and student sides, (2) focusing on the design, development and impact of e-LKM on student learning outcomes, (3) the context of implementation and the use of e-LKM in education in Indonesia, and (4) media innovation and the role of educators in learning process. The findings of this research recommend the need for equitable distribution of research capacity, deepening pedagogical studies, as well as strengthening collaboration across institutions and regions, as well as sustainable innovation to support digital transformation in higher education to develop more inclusive and sustainable e-LKM in Indonesia.